Carotid Atherosclerosis and White Matter Hypodensities: a Controversial Relationship - Félix-Morais, Ricardo; Sargento-Freitas, João; Silva, Fernando; Cordeiro, Gustavo; Nunes, César; Ribeiro, Joana; Cordeiro, Miguel; Moura, Cristina; Cunha, Luis (Acta Médica Portuguesa, 2014)
Introduction: White matter hypodensities of presumed vascular origin, are recognized as an important cause of morbidity with established clinical and cognitive consequences. Nonetheless, many doubts remain on its physiopathology. Our goal is to clarify the potential role of carotid atherosclerosis and other vascular risk factors in the development of white matter hypodensities of presumed vascular origin. Material and Methods: We included patients that underwent CT brain scan and neurosonologic evaluation within a one-month period. Full assessment of vascular risks factors was performed. We seek to find independent associations between white matter hypodensities of presumed vascular origin, carotid intima-media thickness and vascular risk factors. Results: 472 patients were included, mean age was 67.32 (SD: 14.75), 274 (58.1%) were male. The independent predictors of white matter hypodensities of presumed vascular origin were age (OR: 1.067, 95% IC: 1.049 – 1.086, p < 0.001) and hypertension (OR: 1.726, 95% IC: 1.097 – 2.715, p = 0.018). No association was found between IMT (OR: 2.613, 95% IC: 0.886 – 7.708, p = 0.082) or carotid artery stenosis (OR: 1.021, 95% IC: 0.785 – 1.328, p = 0.877) and white matter hypodensities of presumed vascular origin. Discussion: Only age and hypertension proved to have an independent association with white matter hypodensities of presumed vascular origin. Carotid atherosclerosis, evaluated by IMT and the degree of carotid artery stenosis, showed no association with white matter hypodensities of presumed vascular origin. Since atherosclerosis is a systemic pathology, these results suggest that alternative mechanisms are responsible for the development of white matter hypodensities of presumed vascular origin. Conclusion: Age and hypertension seem to be the main factors in the development of white matter hypodensities of presumed vascular origin. No association was found between carotid atherosclerosis and white matter hypodensities of presumed vascular origin. Keywords: Brain; Carotid Artery Disease.